BAL findings in a patient with pulmonary alveolar proteinosis successfully treated with GM-CSF. Issue 3 (1st March 2002) - Schoch, O D; Schanz, U; Koller, M; Nakata, K; Seymour, J F; Russi, E W; Boehler, A
Abstract : Background: Idiopathic pulmonary alveolar proteinosis (PAP) has recently been recognised as a disease of impaired alveolar macrophage function caused by neutralising anti-granulocyte-macrophage colony-stimulating (anti-GM-CSF) autoantibodies. Subcutaneous recombinant human GM-CSF is a novel treatment for PAP, but its mechanism of action is unclear. Methods: Clinical, functional, and bronchoalveolar lavage (BAL) findings were prospectively evaluated in a patient with PAP treated with daily subcutaneous GM-CSF 8 μg/kg for 12 weeks. Results: Treatment resulted in improvements in dyspnoea, lung function, and peak cycle ergometry performance. In serum and BAL fluid the titre of anti-GM-CSF autoantibodies was raised at baseline and markedly reduced on treatment. At baseline the BAL fluid cellular profile showed a decrease in the absolute number and the percentage of macrophages (50%) and an increase in lymphocytes (45%), predominantly CD4+. This cellular distribution remained unchanged after 6 and 12 weeks of treatment while macrophages became morphologically normal and functionally improved. Extracellular proteinaceous material completely disappeared. Conclusions: Clinically successful treatment of PAP with GM-CSF was associated with a profound reduction in GM-CSF neutralising autoantibodies, improvement in alveolar macrophage morphology and function, but persistent BAL lymphocytosis.